Active Learning In Satellite Mission Design - Mohd Dahlan, Siti Fariza; Mohd Yusof, lIIyia (2004)
Designing a satellite mission is a not an easy task as it requires thorough consideration, complex calculations and repeated analysis in determining the best design parameters.